(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1994)
The micropaleontologic study of the oolitic dolomites from the Fkirine Formation, outcropping along the North-South Axis, allows to characterize the Upper Triassic (Norian?-Rhaetian) in Central Tunisia based on the discovery of Agathammines (Hoyenella inconstans and Agathammina austroalpina) and Aulotortus. This "Rhaetian" benthic foraminiferal assemblage, well known in the Peritethyan areas and locally associated with Gandinella falsofriedli, partially occurs in the type-locality of the Fkirine Formation ("Dorsale Tunisienne") and within the Zerzour Formation from the Saharian Shelf (Jeffara).